2011
DOI: 10.1088/0004-637x/732/1/57
|View full text |Cite
|
Sign up to set email alerts
|

Induced Rotation in Three-Dimensional Simulations of Core-Collapse Supernovae: Implications for Pulsar Spins

Abstract: It has been suggested that the observed rotation periods of radio pulsars might be induced by a non-axisymmetric spiral-mode instability in the turbulent region behind the stalled supernova bounce shock, even if the progenitor core was not initially rotating. In this paper, using the three-dimensional AMR code CASTRO with a realistic progenitor and equation of state and a simple neutrino heating and cooling scheme, we present a numerical study of the evolution in 3D of the rotational profile of a supernova cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 24 publications
8
68
0
Order By: Relevance
“…Relevant to the stochastic angular momentum supply are the spiral modes of the SASI (for more on the spiral modes of SASI see, e.g., Hanke et al 2013;Fernández 2015;Kazeroni et al 2016). In that respect it should be noted that Blondin & Mezzacappa (2007), Fernández (2010, and Rantsiou et al (2011) suggest that the the SASI can supply the angular momentum of pulsars. New simulations suggest that the SASI is the main source of the angular momentum, and not pre-collapse convection, although the convection can supply the seed perturbations.…”
Section: The Jittering-jets Modelmentioning
confidence: 99%
“…Relevant to the stochastic angular momentum supply are the spiral modes of the SASI (for more on the spiral modes of SASI see, e.g., Hanke et al 2013;Fernández 2015;Kazeroni et al 2016). In that respect it should be noted that Blondin & Mezzacappa (2007), Fernández (2010, and Rantsiou et al (2011) suggest that the the SASI can supply the angular momentum of pulsars. New simulations suggest that the SASI is the main source of the angular momentum, and not pre-collapse convection, although the convection can supply the seed perturbations.…”
Section: The Jittering-jets Modelmentioning
confidence: 99%
“…(v) It has recently been suggested [17] that due to the standing accretion shock instability (SASI), accretion of matter surrounding the PNS during the first second after the bounce can significantly spin up the PNS. However, subsequent, more accurate numerical simulations found that this process is not effective [18]. The above-listed processes are not fully understood; however, based on current literature, we shall assume that they are not effective in phase 2, i.e., between t ∼ 0.2-0.5 s and t ∼ 1 min after bounce, with the only exception of mass and angular momentum losses through neutrino emission.…”
Section: Introductionmentioning
confidence: 99%
“…The angular momentum source is the convective regions in the core (Gilkis & Soker 2014), and/or instabilities in the shocked region of the collapsing core. Blondin & Mezzacappa (2007), Fernández (2010, and Rantsiou et al (2011) suggested that the source of the angular momentum of pulsars is the spiral mode of the SASI. In the jittering-jet mechanism there is no need to revive the accretion shock, and it is a mechanism based on a negative feedback cycle.…”
Section: Discussion and Summarymentioning
confidence: 99%